Microbial community-based polyhydroxyalkanoates (PHAs) production from wastewater: Techno-economic analysis and ex-ante environmental assessment. (June 2015) - Fernández-Dacosta, Cora; Posada, John A.; Kleerebezem, Robbert; Cuellar, Maria C.; Ramirez, Andrea
Highlights: Fermentation of wastewater towards polyhydroxyalkanoates is scaled-up. Intracellular polyhydroxyalkanoates release by three downstream processes. Process design, techno-economic and life cycle assessment are developed. Key features of the industrial process are identified prior to commercialisation. Sensitivity analysis of the costs and environmental impacts is performed. Abstract: This work investigates the potential for polyhydroxybutyrate (PHB) production from wastewater, from a techno-economic and an environmental perspective, examining scale-up opportunities and bottlenecks prior to commercialisation. Conceptual process design, economic, environmental impacts and sensitivity analysis are developed for one fermentation process and three downstream processing routes, based on alkali, surfactant-hypochlorite and solvent treatments. Environmentally and cost-wise, the alkali treatment is the most favourable with production costs of 1.40 €/kg PHB, global warming potential of 2.4 kg CO2 -eq/kg PHB and non-renewable energy use of 106 MJ/kg PHB. The solvent-based process yields the highest costs and environmental burdens: 1.95 €/kg PHB, 4.30 kg CO2 -eq/kg PHB and 156 MJ/kg PHB. The production of PHB from wastewater is identified as an interesting alternative to pure culture-polyhydroxyalkanoates production from sugars. However, these results are not yet competitive with those for the petrochemical counterparts. Additional performance improvements may be possible, through process integration and optimisation.